2022
DOI: 10.1002/vro2.26
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and allelic frequency of a mutation in the NHEJ1 gene associated with collie eye anomaly in dogs in Italy

Abstract: Background: A 7.8-kb deletion in intron 4 of the NHEJ canine gene is associated with Collie Eye Anomaly (CEA). This deletion has been described in sheep-herding breeds related to the collie lineage and in several other dog breeds. A genetic test based on this association can distinguish three genotypes: normal, carrier and affected. The present study is a retrospective investigation of the presence of the CEA allele frequencies in selected breeds from the Italian dog population over a 10-year time span. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…The mutant allele frequency in our findings was 9.71%, and almost no homozygous mutants were detected (0.26%), similar to reported results from Italian, Czech and Belgian populations [ 8 , 35 , 36 ]. The slightly lower frequency of the mutant allele observed in these studies was probably caused by their relatively small cohort.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mutant allele frequency in our findings was 9.71%, and almost no homozygous mutants were detected (0.26%), similar to reported results from Italian, Czech and Belgian populations [ 8 , 35 , 36 ]. The slightly lower frequency of the mutant allele observed in these studies was probably caused by their relatively small cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Collie eye anomaly (CEA) is a hereditary autosomal recessive disease in sheep-herding breeds caused by abnormal embryonic development, which results in severe eye deformations (choroidal hypoplasia, coloboma, staphyloma and retinal detachment) and, in the final stages, even blindness. This disease was first noticed in 1953 in Rough Collie dogs; since then, more affected breeds have been identified [5][6][7][8]. Collie Rough, Collie Smooth, Border Collie, Shetland Sheepdog and AS appear to be in the same cluster and share a common Collie ancestor, so causative mutation causing CEA in the NHEJ1 gene seems to be identical by descent and is one of the top three most common congenital ocular disorders that affect AS [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…After 2013 and a later court case, Genetic Veterinary Sciences, Inc. v. Canine EIC Genetics, LLC [51], multiple canine genetic testing companies began offering prcd-PRA and CEA tests; thus, the declining numbers are likely best interpreted as testing being conducted by other providers, rather than an actual decrease in testing as both diseases were present worldwide (Figure 1A). Indeed, a 2022 Italian study of five dog breeds reported a 5.24% frequency of CEA NHEJ1 variant homozygotes and a 31.45% carrier rate [41], while a 2019 Brazilian study reported a 25.5% prevalence of the prcd-PRA mutation in English Cocker Spaniels [45]. CEA and prcd-PRA were among the most common disease variants in a 2018 study (100,000 dogs) [13] and continue to be among the most prevalent disease variants in 2023 (over a million dogs) [12].…”
Section: Discussionmentioning
confidence: 99%
“…The same study determined prcd-PRA allele frequencies in mixed-breed dogs and purebred dogs of 3.418% and 1.746%, respectively, which placed prcd-PRA as the 3rd and 2nd most prevalent allele among those respective populations [13]. Other studies using various breeds in different countries have calculated the allele frequency of the CEA deletion at 0.43-79.7% and the prcd-PRA variant at 1.2-45% [14,33,34,[41][42][43][44][45][46][47]. One study tracked disease-causing variants over time in eight breeds for eight single-gene disorders, one of which was prcd-PRA [46].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation